Dampak Disiplin Kerja dan Kompensasi Finansial pada Kinerja - Adi putra, I Nyoman Candra; Trarintya, Mirah Ayu Putri; Mahayoga, Gede Agus Dian (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Maximizing performance is critical to business growth and development in order to maximize overall productivity. Poor employee performance has a negative impact on the company, so it must be maintained and improved all the time. It is hoped that this study will allow us to investigate the impact of work discipline and financial rewards on PT employee performance. Sidraya Star in Mambal, Badung Regency. The total population is 33 of his, so everyone is used as a sample. The analysis method used is multiple linear regression. The results of the analysis performed show that work discipline and financial compensation have a positive and significant influence on performance. It is suggested to the management to always improve the work discipline of employees and provide appropriate financial compensation so that their performance can improve better.